Ginkgo biloba extract mitigates liver fibrosis and apoptosis by regulating p38 MAPK, NF-κB/IκBα, and Bcl-2/Bax signaling - Wang YY; Wang R; Wang YJ; Peng RQ; Wu Y; Yuan YF (Dove Medical Press, 2015)
Yuanyuan Wang, Rong Wang, Yujie Wang, Ruqin Peng, Yan Wu, Yongfang Yuan Department of Pharmacy, Shanghai 9th People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China Background: Liver fibrosis is the consequence of diverse liver injuries and can eventually develop into liver cirrhosis. Ginkgo biloba extract (GBE) is an extract from dried ginkgo leaves that has many pharmacological effects because of its various ingredients and has been shown to be hepatoprotective. Purpose and methods: Aimed to investigate the underlying protective mechanisms of GBE on carbon tetrachloride (CCl4)-induced liver fibrosis in rats. Male Sprague Dawley rats were randomly divided into four groups: control group (C), model group (M), low-dose group (L), and high-dose group (H). Liver fibrosis was induced by CCl4 groups M, L, and H: group C was administered saline. In addition, GBE at different doses was used to treat groups L and H. Results: The results of hematoxylin and eosin staining, Masson’s trichrome staining, a liver function index, and a liver fibrosis index showed that GBE application noticeably mitigated fibrosis and improved the function of the liver. The western blotting and immunohistochemistry analyses indicated that GBE reduced liver fibrosis not only by inhibiting p38 MAPK and NF-κBp65 via inhibition of IκBα degradation but also by inhibiting hepatocyte apoptosis via downregulation of Bax, upregulation of Bcl-2, and subsequent inhibition of caspase-3 activation. Inflammation-associated factors and hepatic stellate cell (HSC)-activation markers further demonstrated that GBE could effectively inhibit HSC activation and inflammation as a result of its regulation of p38 MAPK and nuclear factor-kappa B/IκBα signaling. Conclusion: Our findings indicated a novel role for GBE in the treatment of liver fibrosis. The potential mechanisms may be associated with the following signaling pathways: 1) the p38 MAPK and nuclear factor-kappa B/IκBα signaling pathways (inhibiting inflammation and HSCs activation) and 2) the Bcl-2/Bax signaling pathway (inhibiting the apoptosis of hepatocytes). Keywords: rats, HSCs activation, inflammation, hepatoprotective, mechanism, pathways